The Role of Surrendering to God in Reducing Work-Related Stress Among Office Workers - Amran, Yuli; Lestari, Shalsa Pebi (Public Health of Indonesia, 2024)
Abstract Background:Work-related stress is a common mental health concern among office workers. Surrendering to God during work activities may help prevent or reduce the risk of work-related stress. Objectives:This study aims to examine the correlation between surrendering to God and work-related stress among office workers at the Head Office of Company X. Methods:A cross-sectional study design was used in this research. A total of 149 respondents were selected through simple random sampling. Results:The study found that 24.5% of workers experience work-related stress. It also revealed that higher levels of surrendering to God as measured by dimensions such as effort (ikhtiar), patience, gratitude, acceptance of fate, and faith in God are significantly correlated with lower levels of work-related stress among office workers. Conclusion:It is crucial to promote and enhance the practice of surrendering to God in work environments to help prevent work-related stress among office workers. Organizing training to improve employees' emotional and spiritual management capacities is vital for maintaining their mental health. Keywords:surrendering to god; work-related stress; office workers